Interactivity and User Engagement in Art Presentation Interfaces - Maleshkova, Jeni; Purver, Matthew; Weyrich, Tim; Mcowan, Peter W. (Springer, 2016)
In spite of the rapid technological development in the field of digital image processing and communication, the dominant way of presenting works of visual art virtually is still based on more traditional methods. These are commonly related to the ‘white cube’ exhibition space, which is a popular way of displaying art in museums. Most of the attempts to introduce modern technologies in the digital presentation of visual art are based on the approach of recreating the conventional real environment using realistically rendered two- or three-dimensional computer models. Such forms of presentation fail to take full advantage of the new opportunities, offered by modern digital technologies. In this chapter, we examine through quantitative studies how interactivity in virtual environments can contribute towards visual art presentation. More precisely, we investigate how four interactivity modes through which images of visual art are presented, relate to the different phases of user engagement. The results from our studies indicate that more interactivity in an interactive application contributes towards higher user engagement with the presented content and the application itself.
CRIS-Team Scopus Importer:2022-07-26
Keywords: Exhibition Space; Interactive Application; Interactivity Mode; User Engagement; Virtual Environment